IMPLEMENTASI KEBIJAKAN JAMINAN PEMBIAYAAN PENDIDIKAN DAERAH (JPPD) DI KABUPATEN SLEMAN - , IRAWATI,S.E,AKT., Prof. Dr. Wahyudi Kumorotomo, M.P.P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Policy of Regional Education Funding Guarantee (JPPD) has been run in Sleman since 2009 as one of Sleman Government efforts to enhance the quality of community education specifically for the poor students. This research aims to discover the implementation performance of JPPD policy in Sleman District and the factors that influence the implementation. By combining the qualitative and quantitative method, the data was collected by in depth interviews, observation to informants in the Education, Youth, and Sport Agency, shcools, and JPPD receivers. The data being used was in form of primary data and supported by secondary data to enhance validity of data. The data analysis was conducted by data reduction, presetation and conclusion. The research result concludes that generally the implementation of JPPD policy has runned well, using indicator the amount of JPPD receivers are 79% or 6.171 students from approximately 7,848 poor students of High School/Vocational School in 2012. However, in quality the implementation of JPPD was still lacking on the affordability of JPPD that just limited to the poor students. Other research results showed that the factors of implementation support are: availability of legal basis and explanatory rules, coordination and intensive communication between the Dikpora and schools, dedicated and highly committed human resources support, as well as financial resources support from the local government. Whereas, the factors that inhibit the implementation are the substance of the legal basis has not firmly regulated the good purpose in quantity and quality, the target group, the benefit for the JPPD receivers. Other inhibitors factors are unavailability of poor studentsâ data basis, as well as there are minimum coordination between the policy implementer with the authorized agency in KKM policy.